Polysomnographic Spectrum in Obstructive Sleep Apnoea - Shyamala, K.K.; Khatri, Bidhata (International Journal of Medical Research and Review, 2016)
Introduction: Obstructive sleep apnea (OSA) is a common sleep disordered breathing which is often undiagnosed, unrecognized and under treated represents a major public health problem. It is diagnosed by using overnight Polysomnography. The aim of the study was to analyse the Polysomnographic spectrum in Obstructive sleep apnea. Methods: The study was prospective and observational type which included all patients diagnosed with OSA by overnight polysomnography (AHI≥5 events per hour) who had visited department of pulmonary medicine from September 2015 to August 2016. Their polysomnographic data with relevant clinical data were collected and analysed. Results: The mean age of the study group was 49.74 ± 11.59. Our study showed males (41/50 82%) were predominant with male to female ratio of 4:1. Among 50 patients 41(82%) had severe OSA, 8 (16%) moderate and 1 (2%) with mild OSA. The architecture of sleep in OSA was disturbed; the amount of sleep spent in stage N1 had increased to 15.34±9.18, stage N2 and N3 varied and the amount of sleep spent in REM was decreased (9.06 ± 7.93) with varied sleep efficiency. Respiratory events were more in N3 and REM sleep. With CPAP there was definite increase in the stage N3 (P=0.010) and REM sleep (P=0.0000). There was reduction in RDI (P=0.0000). Conclusion: Overnight polysomnography is the standard test recommended for diagnosis of OSA. OSA significantly affected the sleep architecture, sleep efficiency. Early diagnosis by regular sleep evaluation in routine clinical practice would result in better treatment outcome.